The Principle of Regulation of Mining Business License - La Sensu Sensu; Oheo K. Haris; Muhammad Nazar (Universitas Airlangga, 2021)
The purpose of this study is to see and analyze the substance of a mining business permit regulation for the government to communities around mining and to find out and analyze the basic principles of a government policy to give birth to the welfare of communities around mining. This research used socio-legal research, which is a type of research whose orientation is focused on legal and non-legal aspects, namely the work of law in society and government. This revealed is that (1) the nature of Mining Business Permit Arrangements in regional autonomy has created euphoria among local governments, one of which is the assumption that mining belongs to the region and the local community; (2). Whereas the basic principle of the birth of a policy that does not pay attention to the welfare and interests of the local community will result in environmental damage, disharmony between residents, and the absence of commitment to building from mining entrepreneurs from the community around the mine.